2015
DOI: 10.1111/nana.12135
|View full text |Cite
|
Sign up to set email alerts
|

Nationalism and revolution: friends or foes?

Abstract: Nationalism and revolution have generally been held to go together. Many nation-states have had their origins in revolution, from the Americans in the 18th century to a host of Third World nation-states in the 20th century. Generally, both modern revolutions and modern nationalism have the same origins, in 18th century Enlightenment thought. But this paper argues that, despite this common origin, the principles of revolution and nationalism are divergent, and can set one against the other. Revolutions emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Scholars have found that revolution and nationalism, sharing common pursuits while emphasizing equality and integration respectively, can be either friends or foes, depending on the historical context. For example, Kumar’s (2015) agenda-setting work finds that revolution can foster nation-building, but at times has contradicted it: in the Revolution of 1848, counterrevolutionaries finally sided with romantic nationalism, waging the two movements against each other. Malesevic (2017: 177–88) articulates the mechanisms through which revolution and nationalism are mutually reinforcing: revolution was a mobilizational process whereby the penetration of ideology intensified and organizational capacity developed, which may have led to fervent nationalism.…”
Section: Nationality Models: China’s Deviation From the Soviet Unionmentioning
confidence: 99%
“…Scholars have found that revolution and nationalism, sharing common pursuits while emphasizing equality and integration respectively, can be either friends or foes, depending on the historical context. For example, Kumar’s (2015) agenda-setting work finds that revolution can foster nation-building, but at times has contradicted it: in the Revolution of 1848, counterrevolutionaries finally sided with romantic nationalism, waging the two movements against each other. Malesevic (2017: 177–88) articulates the mechanisms through which revolution and nationalism are mutually reinforcing: revolution was a mobilizational process whereby the penetration of ideology intensified and organizational capacity developed, which may have led to fervent nationalism.…”
Section: Nationality Models: China’s Deviation From the Soviet Unionmentioning
confidence: 99%
“…The works claim that disorientation, dysregulation, disorganization, and the intensification of tensions increased the level of deviant and protest behavior (Mironov, 2015, p. 89;Rendle and Retish, 2017). Although the existing body of work plausibly identifies the structural factors that contributed to the Russian Revolution of 1917, it understudies how political subjects triggered off their revolutionary potential (Kumar, 2015). In other words, the substantive literature avoids scrutinizing Russian political consciousness shaped by the structural factors, perpetuated, distributed and redistributed over time (Rendle, 2005;Cracraft, 2010;Michael-Matsas 2016;Rendle and Lively, 2017).…”
Section: революция которая не произошла: потенциал возрождения русского национализмаmentioning
confidence: 99%
“…Historically, national revolutions and uprisings have taken various shapes such as the activities of the Spanish Falanga, which successfully fought the internationalist Republic, the Nazi upheaval in the 1930s or the Kurdish revival in Iraq in the 2010s. The theoretical aspect of the topic may not have been studied sufficiently; however, some publications concerning the issue are recommended (Unwalla, 2015;Kumar, 2015). Russia can be described as a post-revolutionary country in at least two aspects.…”
Section: Introductory Remarksmentioning
confidence: 99%